1985
DOI: 10.1111/j.1476-5381.1985.tb08873.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diltiazem on noradrenaline release

Abstract: 1 The effects of diltiazem in rat tail arteries and guinea-pig vasa deferentia have been investigated. 2 Superfusion of the rat tail artery with diltiazem (10-6 10-M) resulted in a dose-related increase in 3H-overflow (P < 0.001) both in Wistar Kyoto (WKY) and in spontaneously hypertensive (SHR) rats. Release of 3H by transmural stimulation (I Hz, 2 ms, 10 V) was also much greater in vessels perfused with diltiazem; this effect was dose-dependent. 3 Diltiazem did not significantly alter the proportion of norad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Since the NA-depleting activity of verapamil that is described here was accompanied by a similar reduction in tissue DA and DHPG, it is unlikely that the depletion is due to an altered rate of synthesis or degradation. Other investigators have already established that the NA-depleting activity of verapamil is unaIfected by K+ channel blockade, inhibition of uptake1 and uptakez, or a2-adrenoceptor antagonism induced with yohimbine (Chaudhry & Vohra 1984Wolchinsky & Zsoter 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Since the NA-depleting activity of verapamil that is described here was accompanied by a similar reduction in tissue DA and DHPG, it is unlikely that the depletion is due to an altered rate of synthesis or degradation. Other investigators have already established that the NA-depleting activity of verapamil is unaIfected by K+ channel blockade, inhibition of uptake1 and uptakez, or a2-adrenoceptor antagonism induced with yohimbine (Chaudhry & Vohra 1984Wolchinsky & Zsoter 1985).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that pinacidil directly affects, in a non-specific manner, the storage sites for catecholamines, as does tyramine (Lindmar et al, 1967). Calcium channel blockers, like nifedipine or diltiazem, do have such properties (Wolchinsky & Zsoster, 1985;Zsoster & Wolchinsky, 1986). Moreover, this hypothesis of a 'non-specific' effect agrees with a recent communication from Cook et al (1989) who found, in in vitro experiments, that the vasodilator activity of pinacidil cannot be solely explained by potassium channel opening.…”
Section: Controlsmentioning
confidence: 99%
“…The precise mechanisms responsible for these hemodynamic effects and the inhibited norepinephrine release during diltiazem administration shown in the present study have not been established. In rats, diltiazem has been shown to inhibit norepinephrine release from sympathetic nerve terminals and the adrenal gland through an alteration in adrenergic cardiovascular stimulation [21]. Imai et al [22], however, reported that continuous infusion of diltiazem induced a gradual decrease in both arterial pressure and heart rate in rats, whereas it also induced activation of the sympathetic nervous system, as assessed by the correlation between systolic pressure and norepinephrine.…”
Section: Discussionmentioning
confidence: 98%